EFFECT OF PENETRATION ENHANCER ON THE IN VITRO EX VIVO PERMEATION OF DICLOFENAC GEL - Shinde, Mukesh; Gharge, Vikram; Pimple, Shrikant; Gurjar, Mukund; Shah, Mahesh (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: The objective of this study was to compare and evaluate in vitro ex vivo transdermal potential of the diclofenac sodium (DS) gel by different permeation enhancers using Franz-type diffusion cells. Methods: DS gel was prepared with carbapol, dimethyl sulfoxide, oleic acid (OA), and menthol with 1% w/w concentration each as the penetration enhancer. The in vitro, ex vivo permeability were determined using cellophane membrane and abdominal rat skin. Steady-state flux, permeability coefficient (kp), diffusion coefficient, and lag time were calculated. Results: Menthol, at the concentration of 1% w/w, shows maximum kp, diffusion coefficient permeation enhancement effect with an enhancement ratio 40%, as compared to dimethyl sulfoxide and OA. Conclusion: This finding predicts that DS gel 1% w/w containing menthol 1% w/w can possibly deliver therapeutically relevant dose of DS. Keywords: Diclofenac sodium gel, Menthol, Penetration enhancer, Permeation coefficient. Â Â